'Young People Just Resolve It in Their Own Group': Young People's Perspectives on Responses to Non-Consensual Intimate Image Distribution. (December 2022) - Dodge, Alexa; Lockhart, Emily
While responses to non-consensual intimate image distribution (NCIID) often highlight criminal law remedies, little is known about how young people are choosing to respond to this act and whether they perceive legal intervention as a useful tool. Drawing from interviews with 10 teenagers and survey responses from 81 adult supporters, we provide insight into how young people perceive the supports available to them for responding to NCIID. We find young people may avoid seeking support from both the criminal justice system and adults in general due to fears of adult overreaction, victim blaming and shaming, and self/peer criminalization.